Factors Affecting the Attitudes of Membersâ Towards Participation in Fisheries Cooperative In Dahlak Islands, Eritrea - Chaichan Wongsamun, Daniel Sium, (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The study intended to analyze factors affecting the membersâ attitudes towardsparticipation their cooperative in fishing communities of Dahlak Islands, Eritrea.The Ministry of Marine Resources Eritrea (MMR) initiated the formation offisheries cooperatives in 1994, in 2017 only 39 village level cooperatives and 6regional fishery cooperatives were functional. Considering the fact that activeparticipations leads to successful cooperation, yet only about 1,500 fishermen andwomen were actively incorporated nationwide. Dahlak islands fisheriescooperative was one of the six reginal cooperative with 228 active membersengaged in fish supply services. To understand their attitude, the study usedquantitative approach in collecting data, information was gathered usingquestionnaires from 140 systematically selected random samples with 95%confidence level. To obtain information Likert-type questions were designed,where the data were considered as continuous data and analyzed using StatisticalPackage for Social Sciences. The results showed that attitudes towardsparticipation were positive, with only 11.4% of the respondent having negativeattitudes. The attitudes of members were correlated with independent factors ofage, gender, educational level, monthly income, family size, profession, trainingattendance, number of training taken, loan received and amount of loan received.Sorted from highest to lowest the variables with significant correlation were;number of training taken (0.50**), cooperative related training taken (0.46**),monthly income from Cooperative (0.34**), loan received (0.25**) amount of loantaken (0.20*). In conclusion taking training and number of training taken ofmembers were attributes to active psrticipation, and with the increase in number oftrainings the members had more positive attitudes towards participation. Moreover,the chances of receiving loans and amount of loans had significant effect inincreasing participation. It is recommended to increase the number of traininggiven and accessibility of loans to improve participation of members in fisheriescooperative in Dahlak islands, Eritrea.Key Words: Dahlak, fishery, cooperative, participation, attitude